(+)-catechin protects PC12 cells against CORT-induced oxidative stress and pyroptosis through the pathways of PI3K/AKT and Nrf2/HO-1/NF-κB - Chencen, Lai; Shuo, Zhang; Zhiyu, Chen; Xiaoyu, Fu; Min, Zhang; Pengjiao, Wang; Xiuli, Gao (Frontiers in Pharmacology, 2024)
Pyroptosis induced by oxidative stress is a significant contributor to mental health disorders, including depression (+)-Catechin (CA), a polyphenolic compound prevalent in various food sources, has been substantiated by prior research to exhibit potent antioxidant properties and potential antidepressant effects. Nonetheless, the precise antidepressive mechanisms and effects of CA remain incompletely elucidated. In this study, we employed corticosterone (CORT) and PC12 cells to develop a cellular model of depression, aiming to investigate the protective effects of CA against CORT-induced cellular damage. Our objective was to elucidate the underlying mechanisms of protective action. We utilized transcriptomic analysis to identify differentially expressed genes and employed bioinformatics approaches to predict the potential mechanisms of CA’s protective effects in PC12 cells. These transcriptomic predictions were subsequently validated through western blot analysis. The findings indicated that CA possesses the capacity to mitigate oxidative stress and suppress pyroptosis in PC12 cells via the activation of the PI3K/AKT signaling pathway. This activation subsequently modulates the Nrf2/HO1/NF-κB pathways, thereby providing protection to PC12 cells against damage induced by CORT. Furthermore, we investigated the interaction between CA and the Keap1 protein employing molecular docking and protein thermal shift assays. We propose that CA can activate Nrf2 through two mechanisms to decrease reactive oxygen species (ROS) levels and inhibit pyroptosis: one mechanism involves the activation of the PI3K/AKT signaling pathway, and the other involves direct binding to Keap1, leading to an increase in p-Nrf2.